EPSTEIN BARR VIRUS AND CYTOMEGALOVIRUS CORRELATION WITH ORAL SQUAMOUS CELL CARCINOMA PATIENTS BY USING IN SITU HYBRIDIZATION METHOD IN THE CITY OF BAGHDAD. - Zaid A Saeed; Noor Al-Huda Ali A.H. Saeed; Samar Abdul Raheem Al-Gharrawi (Journal of Global Pharma Technology, 2017)
Worldwide, the most prevalent cancer related deaths, poses one of the most risk cancers globally in many countries, is the oral cancer. There are some important factors associated with many human cancers, for example viral agents, which are involved in the spread of tumors, including the Oral Squamous Cell Carcinoma.So, this study was resolved to determine the relationship between Epstein Barr Virus and Cytomegalovirus with some Iraqi patients who suffer from Oral Squamous Cell Carcinoma by using In Situ Hybridization Technique, related to their age, gender, site distribution, histological grade and the tumor stage.According to sixty OSCC biopsies randomly collected during the period between July 2015 and September 2016, EBV was detected in (71.6 %) 43 out of 60 patients, whereas CMV was detected in (36.6 %) 22 out of 60 patients, the mean age was 38 years old and ranged between ( 27-72) years old, male to female ratio was (1.3 : 1) with 34 men and 26 women, most of the cases were tongue SCC 39, followed by gingiva 13 and 8 were at the floor of the mouth. Histological grades involved were 37 well differentiated, 5 were moderately differentiated and 18 were poorly differentiated. Staging of the tumor included 43 patients who fell in stage I and II, while the rest 17 patients fell in stage III and IV. Regarding to the positive results, EBV correlates in highly significant association with each of (age, gender, grading, tumor stage and site distribution at p<0.01), also CMV correlates with each aspect mentioned above in highly significant association at p<0.05.